Technology and Communication: An Impact study Involving the New Media, College Students, and Communication Patterns - Thangavelu, Tamil Chelivan S.V. (INTI University College, 2010)
The influence of technology can be clearly seen with the use of mobile phones. The dominant use of mobile phones was found to be for social communication (Dimmick, Sikand, & Patterson, 1994). Among residential subscribers, the modal hand-phone call is a pair-wise conversation between friends or family who are located geographically close to each other and who call each other to stay in touch. (Kraut & Mukhopadhyay, 1999) Dordickand LaRose (1992) had a national sample of household records showing whom they talked with, and why. About two-thirds of residential calls were made to family and friends. Mobile phones, on the other hand, are relatively cheap, and a survey indicated that they are owned and used by virtually every student at the University.